Peran Mediasi Komitmen Organisasi pada Pengaruh Kepuasan Kerja terhadap Kinerja Dosen Tetap Universitas Swasta di Kota Medan - Muhammad Adhan; Jufrizen Jufrizen; Muhammad Andi Prayogi; Yudi Siswadi (Universitas Samudra, 2020)
This study aims to analyze the effect of job satisfaction on lecturer organizational commitment and performance, and to analyze the mediating role of organizational commitment to the effect of job satisfaction on lecturer performance. This research was conducted at the Universitas Muhammadiyah Sumatera Utara (UMSU) and the Universitas Muslim Nusantara (UMN) Al Washliyah in Medan. The population is 425 permanent lecturers who hold functional positions at the two universities, and the sample was determined as many as 219 people. Data were collected by interview and questionnaire techniques. Path analysis is used to analyze data, and shows that job satisfaction is proven to have a significant direct effect both on organizational commitment and on lecturer performance. Organizational commitment is also proven to have a direct and significant effect on performance. However. the test results show that job satisfaction does not support lecturer performance when mediated through organizational commitment.